Detection of American Foulbrood Disease (Paenibacillus larvae) By the PCR and Culture - Kilic, Ayse; Simsek, Halil; Kalender, Hakan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
American foulbrood (AFB) caused by Paenibacillus larvae is a bacterial disease in honey bee larvae that is observed worldwide. The aim of this study was to detect P. larvae in honey and beeswax samples from the suspected hives by direct PCR and culture growth. AF6 and AF7, the most sensitive pair of primers, were used to identify the DNA of P. larvae. A total of 100 suspected honey and beeswax samples collected from 25 different enterprises were examined. P. larvae were identified in 7 samples out of 8 by the PCR positive in total. Eight suspected larvae of honeybees were found positive by PCR. A suspected culture-negative sample was found positive through evaluation with PCR. One beeswax sample and seven honey samples were detected as positive for the larvae in the direct PCR detection.
Amerikan yavru çürüklü?ü hastalı?ı etkeni (Paenibacillus larvae)'nin PCR ve kültür ile teşhisi
Keywords: American foulbrood; Culture; PCR; Honey bee